2004
DOI: 10.1007/s00701-004-0256-x
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus pituitary abscess

Abstract: Aspergillus pituitary abscess should be considered in the differential diagnosis of a pituitary mass. The correct diagnosis of pituitary aspergillosis can only be achieved by histopathological examination because clinical and radiological findings including MRI are not specific and culture results are obtained later. Immediately after the diagnosis, intensive antifungal therapy should be started for a successful treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 16 publications
0
44
0
6
Order By: Relevance
“…Some clinical trials have indicated superiority of voriconazole in comparison to amphotericin-B for first-line therapy in patients with Aspergillosis in terms of survival, response rates and safety [13,14]. For the second case the voriconazole was not available, so liposomal amphotericin B was used.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical trials have indicated superiority of voriconazole in comparison to amphotericin-B for first-line therapy in patients with Aspergillosis in terms of survival, response rates and safety [13,14]. For the second case the voriconazole was not available, so liposomal amphotericin B was used.…”
Section: Discussionmentioning
confidence: 99%
“…and Streptococcus spp., followed by Neisseria spp., Micrococcus, Citrobacter spp., Escherichia coli, Brucella, Salmonella, Corynebacterium and Mycobacterium. However, in immunosuppressed patients, Aspergillus, Candida and Histoplasma are the most frequent pathogens [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…and Streptococcus spp., followed by Neisseria spp., Micrococcus, Citrobacter spp., Escherichia coli, Brucella, Salmonella, Corynebacterium & Mycobacterium [5]. However, in immunosuppressed patients, Aspergillus, Candida and Histoplasma are the most frequent pathogens [6]. Preoperative diagnosis is difficult because of rarity of disease, nonspecific symptoms and ring enhancing other pituitary lesions [7].…”
Section: Introductionmentioning
confidence: 99%
“…The responsible microorganisms in abscess formation are common and include several gram-positive and gramnegative bacteria and rarely fungi such as Aspergillus [10,11] or Candida subspecies [12]. Seldom, tuberculous infection of the pituitary was described [13].…”
Section: Discussionmentioning
confidence: 99%